(untitled) - Spring, Joel H. (Boston, 2005)
This current, comprehensive history of American education is designed to stimulate critical analysis and critical thinking by offering alternative interpretations of each historical period. The point of view taken by this text emphasizes 1) the role of multiculturalism and cultural domination in shaping U.S. schools, 2) the position of the school as one of many institutions that manage the distribution of ideas in society, 3) racism as a central issue in U.S. history and U.S. educational history, and 4) economic issues as an important factor in understanding the evolution of U.S. schools.
Keywords: Education,Education,Giáo dục,Giáo dục; History,Social aspects,History,Lịch sử,Khía cạnh giáo dục,Lịch sử; United States,United States,Hoa Kỳ,Hoa Kỳ